Pengaruh Penambahan Ekstrak Daun Ketapang (Terminalia catappa) Terhadap Kualitas Warna dan Efektivitas Pertumbuhan Ikan Molly (Poecilia sphenops) Pada Media Pemeliharaan - Soyasinnisa, Salsabillah; Liubana, Debora Victoria (Jurnal Akuakultur Sungai dan Danau, 2026)
Molly fish or Poecilia sphenops is an ornamental fish species that has economic value and can be cultivated. The main problem often faced by ornamental fish farmers is the fading of fish colors after being kept in aquariums or ponds for a long period of time. This study aims to investigate the effect of ketapang leaf (Terminalia catappa) immersion on the color quality and growth effectiveness of molly fish (Poecilia sphenops) in the maintenance medium. This study involved three treatments, namely aquarium A (100% ketapang leaf extract water), aquarium B (50% ketapang leaf extract and 50% fresh water), and aquarium C (100% fresh water). Each treatment was evaluated based on several test parameters, including color quality percentage, acidity level, dissolved ions, temperature, and total dissolved solids. The results showed that the highest survival rates were found in aquariums B and C, each with a value of 100%. The highest total length growth occurred in aquarium B, reaching 0.33 cm. Aquarium B had the best color quality, with the color most preferred by respondents.